David Foster Wallace, Both Professional and Not. Issue 2 (17th February 2023) - Yu, Timothy
ABSTRACT: Professionals—athletes, journalists, and accountants—feature prominently in the work of David Foster Wallace, remarkable for their single-minded focus on a specialised task. While Wallace finds much to admire in the ideology of professionalism, he is deeply ambivalent about the professional status of the writer and the professionalising effects of academic creative writing. Wallace's essays, his short fiction, and his novel The Pale King often present the professional and the fiction writer as foils. While Wallace invests professionals with remarkable powers, making them seemingly immune to the self-consciousness and self-doubt that plague the writer, the costs of professionalism are ultimately too high, as Wallace refuses the tempting and totalising power of professional ideology in favour of an unprofessional ideal of authorship.